1986
DOI: 10.1002/chin.198636168
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: [Bis(aryloxyacetoxy)iodo]benzenes.

Abstract: The title compounds (III) are synthesized by reaction of [bis(trifluoroacetoxy)iodo]benzene (I) with the salts (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The stable derivatives of aryloxyacetic acid were prepared from their sodium salts and BTI; this approach seems generally more appropriate for the preparation of new iodanes, because of the good nucleofugality of the trifluoroacetoxy anion. In this way it was possible to prepare iodanes from all three isomeric pyridinecarboxylic acids, 47 as well as mixed acyloxy iodanes, 48 such as PhI(OAc)(OOCCF 3 ). Another iodane, PhI(OOCCF 3 )CN, was obtained from the reaction of BTI with Me 3 SiCN in dry CH 2 Cl 2 at -18 o C. 49 The reaction between BTI and potassium phthalimidate 50 (also, sodium saccharinate and other salts from acidic N-H precursors) 51 led to the preparation of several iodanes with two I-N bonds, e.g.…”
Section: Conversion To Other Iodanesmentioning
confidence: 99%
“…The stable derivatives of aryloxyacetic acid were prepared from their sodium salts and BTI; this approach seems generally more appropriate for the preparation of new iodanes, because of the good nucleofugality of the trifluoroacetoxy anion. In this way it was possible to prepare iodanes from all three isomeric pyridinecarboxylic acids, 47 as well as mixed acyloxy iodanes, 48 such as PhI(OAc)(OOCCF 3 ). Another iodane, PhI(OOCCF 3 )CN, was obtained from the reaction of BTI with Me 3 SiCN in dry CH 2 Cl 2 at -18 o C. 49 The reaction between BTI and potassium phthalimidate 50 (also, sodium saccharinate and other salts from acidic N-H precursors) 51 led to the preparation of several iodanes with two I-N bonds, e.g.…”
Section: Conversion To Other Iodanesmentioning
confidence: 99%
“…A characteristic feature of these esters is the carbonyl stretching vibration, which appears at 1 755-1 775 cm-'. The reaction of compound (3) and iodine leading to the formation of compound (4) is the result of a series of distinct reactions, represented by Equations (2)-- (5). From these reactions, Equation (2) has already been mentioned and Equation (3) acids.…”
mentioning
confidence: 99%
“…From these reactions, Equation (2) has already been mentioned and Equation (3) acids. Equation (4) has been the subject of a detailed study between DIBs and alkyl iodides,' where reaction (5) has been suggested as a subsequent step. The decarboxylation products of ArOCH,CO,I are stable compounds and therefore we made independently 2,4-dichloro-a-iodoanisole (5) and found that it reacts not only with compound (3e) to afford compound (6) but also with other DIBs of type (3) providing access to mixed 2,4-dichlorophenoxymethyl aryloxyacetates (6) [Equation (6)].…”
mentioning
confidence: 99%
See 1 more Smart Citation